2008
DOI: 10.1080/07373930802046476
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Vacuum Drying Characteristics of Date Powder

Abstract: Kabkab, Khazravi, and Zark are three varieties of Iranian dates representing high, middle, and low sugar content, respectively. Under the vacuum conditions, powders from these dates were produced and placed in the optimized state for the dehydration reaction. The statistical analyses showed that the moisture reduction range of these three varieties at various conditions (100 C and 15.3 cm Hg, 93 C and 30.4 cm Hg, 84 C and 54.6 cm Hg, 68 C and 60.1 cm Hg) were 17.27±0.16, 20.89±0.19, and 7.61±0.02%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Production of free-flow powder from dates is highly desirable as a stable and convenient nutritious ingredient for use in several food manufacturing applications such as extruded food products, dairy products, and several bakery formulations. Several drying methods were used to produce date powder including, freeze-drying, spray drying, drum drying, vacuum drying, and conventional oven drying (Farahnaky et al, 2016;Manickavasagan et al, 2015;Sablani et al, 2008;Sahari et al, 2008;Seerangurayar et al, 2017). Measurement of powder's physical properties is essential in characterizing their flow properties and, consequently, their behavior during storage, handling, and processing (Barbosa-Cánovas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Production of free-flow powder from dates is highly desirable as a stable and convenient nutritious ingredient for use in several food manufacturing applications such as extruded food products, dairy products, and several bakery formulations. Several drying methods were used to produce date powder including, freeze-drying, spray drying, drum drying, vacuum drying, and conventional oven drying (Farahnaky et al, 2016;Manickavasagan et al, 2015;Sablani et al, 2008;Sahari et al, 2008;Seerangurayar et al, 2017). Measurement of powder's physical properties is essential in characterizing their flow properties and, consequently, their behavior during storage, handling, and processing (Barbosa-Cánovas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that vacuum-dried products are characterized by their better quality retention relative to hot air drying under atmospheric pressure. Vacuum drying has been found to be more effective in drying material with a higher amount of free moisture, such as mango pulp [14], date powder [15], onion slices [16] and yacon slices [17]. However, information about the drying process on oxalate content of vegetable products, especially rice paddy herbs, has not been properly documented.…”
Section: Introductionmentioning
confidence: 99%